Analysis Of Local Government Financial Performance Based On The Method Value For Money - Amril; Ilyas, Muh. Indra Fauzi; Syamsuri, Helmy (International Journal of Business and Social Science Research, 2023)
The purpose of this study was to determine the financial performance of the Makassar City Government based on the Value For Money (VFM) method, namely to analyze the measurement of economic ratios, efficiency and effectiveness (3E). The type of research used is quantitative with a quantitative descriptive approach, namely collecting data, compiling, interpreting, and analyzing it so as to provide conclusions about local government financial performance using Value For Money. The data used is secondary data, namely data on the financial reports of the Regional Revenue and Expenditure Budget (APBD) of the Makassar City Government. The results of the indicate that the economic and efficiency ratios have met the Value For Money standard so that the budget can be more targeted and enjoyed by the community, while the effectiveness ratio has not met the Value For Money standard but there is still a need for continuous improvement in public services so that the effectiveness of government performance is achieved even better in the coming year. But the performance of Makassar City Government as a whole is good.